2019
DOI: 10.1002/xrs.3048
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative determination of macroelement and microelement content of fresh and processed bamboo shoots by wavelength dispersive X‐ray fluorescence spectrometry

Abstract: Bamboo shoots are considered as healthy and nutritional food as they supply proteins, dietary fiber, phenols, phytosterols, vitamins, and minerals in considerable quantities and capture a novel place in the spectrum of plant foods. Besides nutrients and bioactive compounds, shoots also contain antinutrient (cyanogen) that needs to be removed by adequate processing prior to consumption. This study was undertaken to investigate the effects of fermentation, brine preservation, and boiling on levels of mineral ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 22 publications
(26 reference statements)
0
8
0
Order By: Relevance
“…Some minerals, such as Ca and Na, can be entrapped and bonded in complex matrices, which reduce their bioavailability and fermentation usually leads to break these complex molecules (e.g., oxalates and phytate complexes) [69]. The results of Bajwa et al [70] study showed a significant increase in Mg and Ca content and reduction of K after fermentation of D. hamiltonii. The higher mineral content can also be found due to reduction of dry matter during fermentation [71].…”
Section: Changes In Macro-elementsmentioning
confidence: 98%
See 1 more Smart Citation
“…Some minerals, such as Ca and Na, can be entrapped and bonded in complex matrices, which reduce their bioavailability and fermentation usually leads to break these complex molecules (e.g., oxalates and phytate complexes) [69]. The results of Bajwa et al [70] study showed a significant increase in Mg and Ca content and reduction of K after fermentation of D. hamiltonii. The higher mineral content can also be found due to reduction of dry matter during fermentation [71].…”
Section: Changes In Macro-elementsmentioning
confidence: 98%
“…Also, Cu is associated with healthy bones, blood vessels, nerves, and immune function, and it also contributes to Fe absorption. It has been reported that fermentation increases the content of Zn and Fe [70]. However, it was also published that fermentation decreases the concentrations of Cu and Mn [70,72].…”
Section: Changes In Essential Micro-elementsmentioning
confidence: 99%
“…Local people of the study site also informed about its e cacy for edible and medicinal purposes. Across species, ten species had RNVI value in the range of (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), and three species had above 30 index values (Fig. 6).…”
Section: Relative Nutrient Value Index (Rnvi)mentioning
confidence: 99%
“…They may provide employment and economic bene ts to the people of rural areas. Hence, these underutilized plants are put into use as food but now are being projected as healthy food [18][19][20][21][22]. Furthermore, fruits and vegetables also contain a vast and multifaceted array of bioactive secondary compounds that promise to promote good health and protect against many diseases [4,5,23].…”
Section: Introductionmentioning
confidence: 99%
“…Some wild plants have been reported to have good nutritional value than commercialized fruits and vegetables [14]. These plants' higher nutritive value imparts potentially positive effects on human health by lowering the risk of many diseases such as diabetes, cancer, and heart-related disorders [1,[15][16][17]. Therefore, these plants have gained the attention of food scientists, industrialists, farmers, and other stakeholders.…”
Section: Introductionmentioning
confidence: 99%